2011
DOI: 10.1097/brs.0b013e31820712bb
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes Among Low Back Pain Consulters With Referred Leg Pain in Primary Care

Abstract: The clinical course for LBP with self-reported referred leg pain is much worse. However, the fact that differences in outcome were not worse after adjustment suggests that baseline differences in severity and duration of back pain, demographic, and psychological characteristics largely explain the poorer outcomes in patients with referred leg pain. Future research needs to establish if similar results are observed among patients with clinically determined sciatica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 22 publications
3
53
0
1
Order By: Relevance
“…There were little differences in other parameters according to location above and below the knee, although generally patients with LBP + pain below knee in this secondary care setting tended to be more severely affected than those with LBP + pain above knee as previously observed in other settings [20,21]. …”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…There were little differences in other parameters according to location above and below the knee, although generally patients with LBP + pain below knee in this secondary care setting tended to be more severely affected than those with LBP + pain above knee as previously observed in other settings [20,21]. …”
Section: Discussionsupporting
confidence: 72%
“…This has since been shown to be associated with prognosis [18,19], and a recent study in primary care showed that patients with leg pain referred above or below the knee differed on symptom severity as well as psychological characteristics compared with each other and compared with patients who had no pain referral. Importantly, this primary care study also showed that these baseline differences explained most of the variability in outcomes [20]. Other studies have shown that patients with distal leg pain and a positive straight leg test had more severe symptoms, heavier psychological distress and more health care utilization than those without a positive straight leg raise [21,22].…”
Section: Introductionmentioning
confidence: 68%
“…A lumbar disc herniation is the most common cause of sciatica [3,4]. Sciatica is associated with more severe pain and disability than is low back pain alone [5]. Most patients receive conservative treatment, and a minority of patients requires surgery [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…About 60% of patients with low back pain (LBP) report pain in the leg (s) [1] although not all will be diagnosed as having sciatica. Sciatica is a common variation of LBP presenting with radiating pain in the leg and often accompanied by variable neurological changes in sensation, reflex or muscle strength in the leg [2].…”
Section: Introductionmentioning
confidence: 99%